PEMBERDAYAAN KELOMPOK TUKANG BANGUNAN UNTUK MENGATASI RISIKO BANGUNAN RAWAN LONGSOR DI DESA PERKEBUNAN BUKIT LAWANG - Silitonga, Ernesto Maringan Ramot; Qarinur, Muhammad; Sibuea, Dody Taufik Absor; Batubara, Hamidun; Hutagaol, Parlaungan (Bangun Rekaprima, 2024)
Following the flash flood in Bahorok in 2003, concerns about potential similar disasters in the future have been on the rise among both the community and the government. However, economic demands in the vicinity of the affected area have led the community to continue utilizing the riverbanks for building purposes, particularly for nature tourism. This land use has resulted in the narrowing of the river, leading to floods and landslides. Therefore, the less skilled construction workers, who are partners in this initiative, require assistance from the proposing team to provide training in building construction, especially in landslide-prone areas. This training is expected to be a solution to address the issue. Through the exchange of ideas with the proposing team, the partners can enhance their understanding of anticipating building damages due to errors in construction methods. After the training, the community will have a guide for planning and constructing buildings in landslide-prone areas, creating a safe and comfortable environment for both the local residents and tourists visiting Bukit Lawang.